2020
DOI: 10.1002/anie.202006366
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Vinylcyclopropane Reactivity: Palladium‐Catalyzed Asymmetric [5+2] Dipolar Cycloadditions

Abstract: Vinylcyclopropanes (VCPs) are commonly used in transition‐metal‐catalyzed cycloadditions, and the utilization of their recently realized reactivities to construct new cyclic architectures is of great significance in modern synthetic chemistry. Herein, a palladium‐catalyzed, visible‐light‐driven, asymmetric [5+2] cycloaddition of VCPs with α‐diazoketones is accomplished by switching the reactivity of the Pd‐containing dipolar intermediate from an all‐carbon 1,3‐dipole to an oxo‐1,5‐dipole. Enantioenriched seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(19 citation statements)
references
References 98 publications
1
18
0
Order By: Relevance
“…(43b) closed the ring and gave cyclobutyl iminium ions (43c) which could further release the desirable products (39) and finish a catalytic cycle. Bach et al found a co-catalytic system with ruthenium catalyst (Ru(bpz) 3 (PF 6 ) 2 ) and a chiral secondary amine catalyst (44) to synthesize cyclobutanecarbaldehydes (45) from α,β-unsaturated aldehydes (46) and olefins (47) upon the irradiation of visible light (λ = 458 nm) in moderate to good yields and enantioselectivity (49-74% yield, 83-96% er) (Scheme 11) [21]. A variety of substituents such as bromo, chloro, trifluoromethyl, methoxy, pinacolatoboryl, and acetoxy groups at the aryl moiety of α,β-unsaturated aldehydes are reliable substrates.…”
Section: Enantioselective Formation Of 4-membered Ring By Visible Light Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…(43b) closed the ring and gave cyclobutyl iminium ions (43c) which could further release the desirable products (39) and finish a catalytic cycle. Bach et al found a co-catalytic system with ruthenium catalyst (Ru(bpz) 3 (PF 6 ) 2 ) and a chiral secondary amine catalyst (44) to synthesize cyclobutanecarbaldehydes (45) from α,β-unsaturated aldehydes (46) and olefins (47) upon the irradiation of visible light (λ = 458 nm) in moderate to good yields and enantioselectivity (49-74% yield, 83-96% er) (Scheme 11) [21]. A variety of substituents such as bromo, chloro, trifluoromethyl, methoxy, pinacolatoboryl, and acetoxy groups at the aryl moiety of α,β-unsaturated aldehydes are reliable substrates.…”
Section: Enantioselective Formation Of 4-membered Ring By Visible Light Catalysismentioning
confidence: 99%
“…In 2020, Xiao et al found a new asymmetric [5+2] dipolar cycloadditions of vinylcyclopropanes (160) and α-diazoketones (161) to synthesize 7-membered lactones (162) upon the diffraction of blue LED light in good yields and enantioselectivity (52-92% yields, up to 99% er) (Scheme 35) [45]. Pd 2 (dba) 3 •CHCl 3 and a chiral ligand (163) acted as catalysts.…”
Section: Enantioselective Formation Of 6-membered Ring By Visible Light Catalysismentioning
confidence: 99%
“…Due to their congested chemical environment, construction of all-carbon stereogenic centers is a challenging project. 1 And, when vicinal all-carbon quaternary stereocenters are present in one molecule, they will dramatically increase its synthetic challenge. Multiple chemical transformations are normally required to build this structural motif.…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal-catalyzed cycloaddition relying on Tsuji–Trost chemistry has recently emerged as a valuable approach toward π-allyl-Pd II 1, n -zwitterionic dipoles. Following the pioneering work of Zhao, vinylethylene carbonates (and, to a lesser extent, the corresponding oxiranes) have recently gathered growing attention as readily available oxa-1,5-dipole precursors (Scheme a). , The relevance of nitrogenated heterocycles prompted organic chemists to study new aza-dipoles . Tunge and others demonstrated the versatility of vinyl benzoxazinones in a wide array of Pd-catalyzed (4+ n ) cycloadditions (Scheme b) .…”
mentioning
confidence: 99%